The effect of on-line hemodiafiltration on improving the cardiovascular function parameters in children on regular dialysis - Fatina I Fadel; Samuel H Makar; Hanan Zekri; Dina H Ahmed; Ahmed H Aon (Saudi Journal of Kidney Diseases and Transplantation, 2015)
The cardiovascular disease is an important cause of morbidity and accounts for almost 50% of deaths in patients undergoing maintenance dialysis. Many harmful molecules of the uremic milieu, such as the middle molecules, are difficult to remove by conventional hemodialysis (HD). On-line hemodiafiltration (OL-HDF) can achieve a considerable clearance of middle molecules and, together with its sterile ultrapure infusate, may have favorable effects on inflammation and cardiovascular complications. We aimed in this study to assess the effect of OL-HDF on improving the chronic inflammatory state associated with chronic kidney disease and the possible impact of these changes on myocardial function in chronic HD children. Thirty pediatric patients [12 (40%) males and 18 (60%) females with a mean age of 11.3 ± 3.2 years] on conventional HD for at least six months were switched to OL-HDF for six months. Variables for comparison at the end of each period included the levels of serum C-reactive protein and Kt/V as well as electrocardiography and echocardiographic measurements, including left ventricular mass index (LVMI). On changing from HD to OL-HDF, there was a significant decrease in hs-CRP (from 7.9 ± 8.9 to 3.4 ± 3 μ g/mL) (P = 0.01) and frequency of diastolic dysfunction (P = 0.04), while systolic function (FS and EF) improved significantly (P = 0.007 and 0.05, respectively), while LVMI did not change. We conclude that OL-HDF was well tolerated in children with improvement of the systolic function of the myocardium and the overall frequency of diastolic dysfunction.